A Highly Effective Thickener and Stabilizer of Xanthan 80 (SF) Applied to Strengthen the Performance of Solid Microbial Fuel Cells - Wang, Chin Tsan; Lin, Tsung Hung; Chen, Yu Jen; Chong, Wen Tong (American Scientific Publishers, 2017)
Facing the serious issues of using chemical agents in agro-industry and polluting the soil and water sources, the solid microbial fuel cells (SMFCs) would be one of the solutions for managing this problem by undergoing a compost bio-chemical process to degrade solid waste effectively and a driven voltage existed between the electrodes of anode and cathode will transfer electrons from anode to cathode by way of external circuit line for giving the power generation. Now, facing the fact that the water content directly impacts the degrading performance of SMFCs during the composting process, a technique of the highly effective thickener and stabilizer using Xanthan 80 Smoother flow (SF) and a drainage design would be utilized in the system undergoing a series of studies to evaluate its performance on SMFCs. Results show that using Xanthan 80 (SF) can enhance the power performance of SMFCs significantly because of its excellent ability to keep the compost moist throughout and prevent the gravitational effect from the accumulation of water at the bottom of the chamber. These findings will be useful to the modification of SMFCs in the future.